Electroactive Nanogel Formation by Reactive Layer-by-Layer Assembly of Polyester and Branched Polyethylenimine via Aza-Michael Addition - Yildirimkaraman, Oyku; Özenler, Sezer; Gunay, Ufuk Saim; Durmaz, Hakan; Ylldlz, Ümit Hakan (Langmuir, 2021)
We here demonstrate the utilization of reactive layer-by-layer (rLBL) assembly to form a nanogel coating made of branched polyethylenimine (BPEI) and alkyne containing polyester (PE) on a gold surface. The rLBL is generated by the rapid aza-Michael addition reaction of the alkyne group of PE and the -NH2 groups of BPEI by yielding a homogeneous gel coating on the gold substrate. The thickness profile of the nanogel revealed that a 400 nm thick coating is formed by six multilayers of rLBL, and it exhibits 50 nm roughness over 8 μm distance. The LBL characteristics were determined via depth profiling analysis by X-ray photoelectron spectroscopy, and it has been shown that a 70-100 nm periodic increase in gel thickness is a consequence of consecutive cycles of rLBL. A detailed XPS analysis was performed to determine the yield of the rLBL reaction: the average yield was deduced as 86.4% by the ratio of the binding energies at 286.26 eV, (C═CN-C bond) and 283.33 eV, (CC triple bond). The electrochemical characterization of the nanogels ascertains that up to the six-multilayered rLBL of BPEI-PE is electroactive, and the nanogel permeability had led to drive mass and charge transfer effectively. These results promise that nanogel formation by rLBL films may be a straightforward modification of electrodes approach, and it exhibits potential for the application of soft biointerfaces.
CRIS-Team Scopus Importer:2021-09-24